Rice seedling diagnosis of light and water stress based on green – blue channel feature enhancement - Shaowen Liu; Liwei Wang; Zhigang Zhang; Haoran Xu; Yubo Yang; Rui Gao; Zhongbin Su (Computers and Electronics in Agriculture, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

DSAP-WeedNet: A Down-Scale Attention-Guided Lightweight Network for Real-Time Weed Detection Enabling Precision Control in Potato Fields - Lei Han; Yi-Teng Wu; Ke-Jun Fan; Rui-Feng Wang; Wen-Hao Su (Potato Research, 2026)

Long-term cattle manure application rebuilds topsoil buffering capacity and mitigates fertilizer-induced acidification in Mollisols - Yafei Su; Wenbin Bao; Zhenhua Yu; Xiaojing Hu; Changkai Liu; Rui Fang; Junjie Liu; Jian Jin; Guanghua Wang; Xingyi Zhang; Yuriy Kravchenko; Xiaobing Liu; et al. (Agriculture, Ecosystems & Environment, 2026)

Cuproptosis in hepatocellular carcinoma: bridging copper homeostasis with therapeutic horizons - Songsong Fan; Aoqing Wang; Rui Peng; Jun Cao; Daoyuan Tu; Bingbing Su; Jiahao Zhang; Shengjie Jin; Guoqing Jiang; Chi Zhang; Dou-Sheng Bai (Molecular Biology Reports, 2026)

Vegetation conversion and microtopography jointly regulate soil microbial necromass in floodplain wetlands - Xiaomin Zhang; Yakov Kuzyakov; Rui Su; Siwen Hu; Qinglong L. Wu; Dayong Zhao; Jin Zeng (CATENA, 2026)

Decoupled active in-row following strategy for collaborative tobacco-harvesting robots based on ultra-wideband localization and visual perception - Rui Su; Juan Li; Cheng Liu; Ling Wang; Lei Gao; Delun Li; Du Chen (Computers and Electronics in Agriculture, 2026)

Physics-informed graph inference and prediction for global state estimation in water distribution networks - Yacan Man; Xiao Zhou; Wenchong Tian; Rui Yuan; Kuizu Su; Zhiguo Yuan (Water Research, 2026)

Immunomodulatory effects of three herbal extract formulations on bovine peripheral blood mononuclear cells - Xi-Rui Xiang; Eun-Seo Lee; Jun Ho Lee; Su Min Kyung; Han Sang Yoo (Veterinary Immunology and Immunopathology, 2026)

Structurally diverse sesquiterpenoids from Curcuma longa and their anti-inflammatory activities - Guang-Han Li; Chun-Mei Qiu; Guang-Xu Wu; Miao Dai; Rui Feng; Hai-Guo Su; Liang Xiong (Phytochemistry, 2026)

Flow field fitting analysis of earth-rock dam leakage based on an image-based hybrid Quadtree-SBFEM - Binghan Xue; Yahao Bu; Shuaihao Su; Siye Zhang; Jianwei Lei; Rui Pang; Jun Liu (Journal of Applied Geophysics, 2026)

Heterogeneous rock abundances in the lunar subsurface revealed by cold-spot craters - Yizhen Ma; Zhiyong Xiao; Yichen Wang; Yiren Chang; Rui Xu; Yan Su (Icarus, 2026)

Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

Beyond flavor: dietary vanillyl alcohol, a D₂ receptor antagonist promoting sleep - Lijing Zhang; Yujie Yang; Dongmei Yang; Richard Ward; Zhenshuai Hu; Hao Chen; Mengli Lan; Cheng Xiang; Su An; Jiameng Dai; Ying Zhu; Xianrun Sun; et al. (Food Research International, 2026)

The journey of fluxapyroxad, mandipropamid and mefentrifluconazole residues in two morphologically distinct chilli peppers: A comprehensive risk assessment from field to processing - Kai Cui; Rui Ni; Wanru Su; Liping Fang; Ruiyan Ding; Shuai Guan; Jingyun Liang; Jian Wang; Zhan Dong (Food Chemistry, 2026)

Bioinspired ZIF-derived carbon architectures for corrosion-resistant broadband electromagnetic attenuation - Sihao Dou; Yutan Jiang; Yuxiang Zheng; Rui Gao; Zhiyuan Dan; Minghao Yang; Qiang Su; Dongdong Liu; Bo Zhong; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

A dual-state emission NIR fluorescent sensor for intelligent dual-analyte detection and multisite imaging: From N2H4/ClO− and fingerprints to living cells and organisms - Su-qian Cai; Bo-wen An; Rui-yong Jiang; Shang-wei Yuan; Xin Xiao (Analytica Chimica Acta, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Development of CRISPR/Cas9 based precision genome editing tools in grouper in vitro and in vivo - Zeming Zhang; Zehong Su; Wenjie Cheng; Rui Zheng; Jie Gao; Jianguo He; Junjiu Huang; Junfeng Xie (Aquaculture, 2026)

Driving workload capacity of highway tunnel entrance and exit takeover under non-driving-related tasks: a multi-dimensional information coupling method - Shuangkai Zhu; Bo Liang; Jia An Niu; Rui Su; Haonan Long; Tao Deng; Mengdie Xu (Tunnelling and Underground Space Technology, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Melatonin alleviates chilling injury in postharvest banana fruit by modulating membrane lipid and phenolic metabolism - Jing Lin; Rui Zhang; Qi Chen; Weiqi Liang; Yanting Wu; Wenbing Su; Wei Wei; Hetong Lin; Zhongqi Fan (Postharvest Biology and Technology, 2026)

Anti-lipotoxic alkaloids from the roots of Polyalthia cerasoides - Feifei Liu; Xinyi Liu; Yue Chen; Rui Su; Meilan Zhou; Jin Liu; Zhongping Jiang; Yong Rao; Ling Huang (Phytochemistry, 2026)

Incompleteness-aware radar-vision fusion transformer framework for water-surface object detection - Qingwang Han; Ruidan Su; Jialin Wang; Rui Gao; Li Zhou (Ocean Engineering, 2026)

LhCAT2-mediated crosstalk between reactive oxygen species homeostasis and anthocyanin biosynthesis enhances zinc tolerance in Liriodendron hybrid - Yongchao Ke; Yu Liu; Teja Manda; Tian Min; Rui Wang; Wenbin Su; Liming Yang (Journal of Hazardous Materials, 2026)

A Porous Zn-Salen-Based Organic Ionic Polymer as a Robust Bifunctional Catalyst for CO2 Fixation via Epoxide Cycloaddition - Guo-Ling Li; Rui-Yao Qin; Meng-Meng Wang; Qing Li; Shijian Lu; Jin-Shui Su; Qi Zhang; Yun Zhao; Ran Zhang; Zhong-Hai Ni (Journal of Environmental Chemical Engineering, 2026)

Multi-omics integration of flavor metabolome and lipidome elucidates 1-methylcyclopropene effects on postharvest quality in yellow-fleshed peach at 30 °C - Xianan Zhang; Rui Han; Zhengwen Ye; Mingshen Su; Huijuan Zhou; Jihong Du; Minghao Zhang; Feng Leng; Huayu Liu; Xiongwei Li (Food Research International, 2026)

Stress-homogenized and solvation-regulated biomass hydrogel inducing Zn (101) epitaxial growth for ultra-stable anodes - Aoxue Lang; Yongfa Huang; Tingzhen Li; Rui Zhong; Linxuan Su; Zhendong Liu; Jianyun Gan; Ren Zou; Yuan He; Emmanuel Iwuoha; Usisipho Feleni; Kasim Ocakoglu; et al. (Chemical Engineering Journal, 2026)

Tick-type Schottky contact engineering via Ni-CoOx interlayer for enhanced electron transfer in PEM water electrolyzers - Weiding Wang; Kaini Zhang; Hao Wang; Rui Zhao; Chuanjie Lin; Luning Li; Xinzhe Li; Jinzhan Su; Liejin Guo (Chemical Engineering Journal, 2026)

Xylose metabolic engineering of Issatchenkia orientalis for 3-hydroxypropionic acid production from cellulosic hydrolysate without nutrient supplementation - Lin-Rui Tan; Saint Moon Kim; Young B. Cho; Shih-I Tan; Narendra Naik Deshavath; Na Wei; Vijay Singh; Yasuo Yoshikuni; Huimin Zhao; Yong-Su Jin (Bioresource Technology, 2026)

Trade-off mechanisms between N2O emissions and nitrogen multifunctionality in a lake littoral mesocosm wetland under seasonal water-level fluctuations: insights from metagenomics and machine learning - Rui Su; Dayong Zhao; Xiaomin Zhang; Qinglong L. Wu; Jin Zeng (Water Research, 2026)

Co-hydrothermal carbonization of textile dyeing sludge and typical textile wastes: Feedstock-dependent hydrochar performance for adsorption and fuel applications - Rui Zhang; Chenyu Wang; Han Zhou; Weibo Sun; Ying Su; Zehua Zhao (Waste Management, 2026)

On-chip squeezed light in the audio frequency band - Xuezhi Zhu; Yunyun Cao; Rui Liu; Yaya He; Fan Zhang; Yaqing Zhang; Shiwei Du; Meihong Wang; Xiaoshun Jiang; Xiaolong Su (Science Bulletin, 2026)

Near-real-time mapping for causal agents of forest disturbances in China using harmonized Landsat and Sentinel-2 dataset - Ronghua Liao; Chengcheng Guo; Lingkun Chen; Yulin Jiang; Yuchen Tao; Jiani Liao; Rui Lu; Huaguo Huang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2026)

Scale-aware triple collocation: optimizing spatiotemporal windows for enhanced multi-source fusion of meteorological data - Zhixin Peng; Lingjie Li; Yintang Wang; Guoqing Wang; Yong Liu; Zhaode Yun; Rui Gao; Leizhi Wang; Xin Su (Journal of Hydrology, 2026)

Dynamic sulfidation process of nanoscale zero-valent iron induced by sulfate-reducing bacteria and its effect on the reductive dechlorination of trichloroethylene - Shaoyu Wan; Lijuan Zhang; Siqi Zhuang; Yi Su; Qi Liang; Rui Shen; Shanquan Wang; Andrei Ivanets; Bekchanov Davronbek; Xintai Su (Environmental Research, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Post-combined prestressed continuous composite bridge deck for mitigating concrete cracking: Experiment, numerical simulation, and theoretical analysis - Qingtian Su; Rui Zhao; Zhanchong Shi; Disheng Zou; Lefei Huang; Feiran Li; Hui Luo (Engineering Structures, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Pseudofrenelopsis (Cheirolepidiaceae) from the Lower Cretaceous of northwestern China and its paleoclimatic and biogeographic significances - Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Cretaceous Research, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Rate-dependent effects on mechanical properties and particle breakage of red-stratum mudstone fillers - Guoqing Cai; Yanlin Su; Bowen Han; Rui Yang; Xianfeng Diao; Jian Li (Transportation Geotechnics, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Invasive giant African snails as potential reservoirs of antimicrobial resistance and bacterial pathogens in urban park - Yiyue Zhang; Zhonghui Tang; Huayuan Shangguan; Rui Zhu; An Xie; Qiansheng Huang; Jianqiang Su; Patrick O'Connor; Yong Jiang; Xin Sun (Journal of Environmental Management, 2026)

N-myristoyl Transferase Maintains Type II Neuroblasts through Notch Signaling in Drosophila - Sifan Gong; Shuliu Zhang; Xu Yan; Wenting Gong; Qingxia Zhou; Xiaojing Yang; Kun Yang; Menglong Rui; Su Wang (Neuroscience Bulletin, 2026)

NCAPG reprograms glycolytic and lipid metabolism by sustaining glycerophospholipid flux in small-cell lung cancer - Yang Sun; Jinglin Wen; Rui Su; Linlin Liu (Molecular and Cellular Biochemistry, 2026)

Coordinated Control of Automatic Drilling Feed and Heave Compensation for Offshore Hydraulic Hoisting Systems: A Co-Simulation Study - Jingxi Lei; Qiang Wang; Huan Li; Rui Su; Lijun Wang; Chao Liu (Journal of Marine Science and Engineering, 2026)
Offshore drilling operations face the critical challenge of maintaining precise weight-on-bit (WOB) control during automatic drilling feed while subjected to vessel heave disturbances. This study investigates an integrated closed-circuit hydraulic cylinder lifting system that combines full-stroke drill string compensation with potential energy recovery capabilities, addressing the control coupling problem inherent in traditional split-design systems. A longitudinal vibration model of the drill string is established using lumped mass, stiffness, and damping principles incorporating the Rayleigh method. A co-simulation model implementing nested PID control logic is developed on the AMESim platform to evaluate automatic drilling feed performance under both passive and semi-active compensation modes. Simulation results demonstrate that the proposed integrated control strategy effectively mitigates bottom-hole WOB fluctuations, with top drive velocity accurately tracking set drilling feed rates (0.01–0.02 m/s) within a response time of approximately 10 s. The system maintains operational stability under sea conditions up to Grade 6 (heave wave height ≤ 4.578 m, period 14 s), beyond which accumulator piston limit-stroke collision risks emerge. These findings validate the feasibility of integrated hoisting-compensation design and establish quantitative operational limits, providing theoretical foundations for next-generation marine drilling systems targeting ultra-deepwater and natural gas hydrate exploitation.

An Attention-Enhanced Temporal Convolutional Network for Surrounding Rock Deformation Prediction in Mountain Tunnels - Rui Su; Yitao Yang; Guowen Xu; Ziqian Yang; Jie Yu; Ruohui Wang; Dong Zhou; Zhuolin Wu (Rock Mechanics and Rock Engineering, 2026)

Robust under-canopy navigation path extraction for collaborative harvesting robots using semi-supervised UniMatch V2 segmentation enhanced by edge-contour keypoint clustering - Rui Su; Cheng Liu; Zhentao Zhu; Ling Wang; Xu Mao; Lei Gao; Du Chen (Computers and Electronics in Agriculture, 2026)

Evaluation of liver toxicity in rats exposed to silver nanoparticles – Targeted metabolomics and histology based study - Su Rui; Wang Yueyang; Han Zezhou; Cui Yunlong; Li Jianguo (Toxicology and Applied Pharmacology, 2026)

Integrated analyses of whole transcriptome and lipidome using WGCNA to identify regulatory factors associated with different hair types in cashmere goats - Wenze Li; Gao Gong; Wenxin Zheng; Zhiying Wang; Rui Su; Qi Lv (Small Ruminant Research, 2026)

Association of dietary intake of copper and zinc with systemic inflammation: A cross-sectional study integrating machine learning - Xuefei Zhang; Yuqing Deng; Huan Su; Xueran Huang; Yongfen Gao; Zhuangzhuang An; Zouyan He; Dan Li; Haiying Zhang; Rui Lin (Journal of Trace Elements in Medicine and Biology, 2026)

Magnesium isotope geochemistry in continental flood basalts: implications for mantle source heterogeneity - Sakine Moradi; Lie-Meng Chen; Peter C. Lightfoot; Kang-Jun Huang; Qiao Su; Song-Yue Yu; Li-Juan Zhu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

Improved methods for site classification using statistical analysis of ground motion records - Xiaofang Cheng; Xiaojun Li; Ren Deng; Teng Li; Dingding Xiong; Rui Su (Engineering Geology, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Rhizosphere microbial carbon utilization stimulates soil phosphorus fraction transformation in response to maize (Zea mays L.) and soybean (Glycine max.) interspecific interactions - Ruixue Wang; Lizhen Su; Dingjin Li; Zikun Yang; Rui Feng; Yi Zheng; Li Tang (Plant and Soil, 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

Microcavitary Alginate Hydrogel Reverses Chondrocyte Dedifferentiation via Temporal Modulation of the p53 Pathway - Yongchang Yao; Weixian Su; Yupeng Nie; Haoyang Sun; Rui Wang; Rixu Liu; Weiqiang Dong (Annals of Biomedical Engineering, 2026)

Recycling aluminum-rich drinking water treatment sludge into ceramic membranes: Fabrication process and environmental impact assessment - Pu Li; Kunbo Wu; Wenhao Su; Zhiming Chen; Guofen Rui; Mingguo Peng; Jie Teng (Process Safety and Environmental Protection, 2026)

Reconstruction of atmospheric CO2 concentration changes during the Aalenian (Middle Jurassic) based on fossil cuticles of Ginkgoites and Czekanowskia from northwestern China - Yu Jiang; Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A sustainable approach for bauxite residue utilization: Elucidation of high-efficiency reduction mechanisms driven by renewable biochar - Rui Zhang; Qin Wang; Shuojia Song; Siyu Su; Ting-an Zhang (Chemical Engineering Journal, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

Synergistic effect of tetrapropylammonium hydroxide and urea on hemicellulose fractionation with high-purity and high molecular weight - Rui Tian; Yi Ding; Bolang Zhu; Zhenhua Su; Baozhong Lü; Jing Bian; Mingfei Li; Zhengjun Shi; Pai Peng; Yuetong Kang; Feng Peng (Carbohydrate Polymers, 2026)

Development of a portable electrochemical sensor based on STAB-GN for simultaneous detection of chloramphenicol and enrofloxacin in foods - Rui Gao; Yongfeng Chen; Yu Su; Geoffrey I.N. Waterhouse; Xuguang Qiao; Yufeng Sun; Zhixiang Xu (Analytica Chimica Acta, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

The hidden cost of urban noise: spatiotemporal heterogeneity, environmental burden, and economic valuation across major Chinese cities - Zeyu Xu; Rui Hu; Haoran Su; Zhexi Wang (Environmental Monitoring and Assessment, 2026)

Dynamic seepage analysis of unsaturated subgrade bed for ballastless track considering rainfall and train loading - Yanfei Pei; Yipeng Lai; Kaiwen Liu; Rui Su; Ping Wang (Soil Dynamics and Earthquake Engineering, 2026)

Conversion of waste steel slag into recyclable carbon capture adsorbent: stabilizing effect of Ca2MnO4 on calcium looping process - Shuoyang Liang; Aikelaimu Aihemaiti; Yiping Su; Rui Li; Zuotai Zhang (Resources, Conservation and Recycling, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

A COF-spaced Plasmon-enhanced fluorescent nanocomposite for ultrasensitive and on-site dual-modality lateral flow immunoassay - Han Han; Junhua Su; Zhenzhen Liu; Zijin Tong; Lei Wu; Shihui Zhu; Wentao Zhao; Baohua Zhao; Rui Xiao (Chemical Engineering Journal, 2026)

Electronic structure engineered Fe-ZnO@au-DTNB nanotags for ultrasensitive SERS-based lateral flow immunoassay - Renjie Xiong; Junhua Su; Shizhe Wang; Zijin Tong; Renlong Zhu; Yufei Liu; Rui Xiao (Chemical Engineering Journal, 2026)

Selection of targets for cancer mRNA vaccines: from laboratory to clinical application - Huacong Lu; Rui Wu; Xiaodong Su; Fusheng Liu; Sisi Liu; Junwen Zhang (Science China Life Sciences, 2026)

The biphasic regulatory effect of adenosine A2B receptor in ischemic brain injury and its therapeutic potential - Xu Rui; Wang Xi; Li Mengzhu; Su Peiwei; Liu Mudong; Zhu Chao; Luo Wanyu; Zhao Haijun (Purinergic Signalling, 2026)

Integrative Analysis the Role of ENG as a Metabolic and Macrophage-Related Gene in Hepatocellular Carcinoma - Songsong Fan; Yuhong Tang; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Weidi Yu; Chen Chen; Shunyi Wang; Shengjie Jin; Guoqing Jiang; Chi Zhang; et al. (Biochemical Genetics, 2026)

Spatial Distribution Characteristics of Secondary PM2.5 in Beijing-Tianjin-Hebei Region Based on Time Series Decomposition - Qing Yao; Jing Ding; Zi-rui Liu; Xu Yang; Ying-xiao Tang; Zi-yin Cai; Su-qin Han (Aerosol Science and Engineering, 2026)

Correction to: Urban perception analysis: integrating street view imageswith eye-tracking data - Jing Jin; Huifu Li; Rui Zhou; Su Li; Abdureyim Raxidin; Xun Zhang (Environment, Development and Sustainability, 2026)

Physics-informed neural network for predicting longitudinal deformation in super-large-diameter shallow-buried shield tunnel during construction - Xing-Tao Lin; Qi-Rui Lin; Rui-Di Chen; Xiangsheng Chen; Dong Su (Tunnelling and Underground Space Technology, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

From resistance to detection: The role of nanomaterials in plant stress responses - Jing-wan Zhang; Rui-Rui Hao; Abolghassem Emamverdian; Wen-Xun Su; Xing-Hao Zhang; Meisam Zargar; Mo-Xian Chen; Fu-Yuan Zhu (Plant Science, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Dimeric alkenyl α-pyrones from Cryptocarya calcicola with their cytotoxicity - Yu Liu; Wei Li; Yu Su; Li Rao; Qian He; Yun-Xia You; Chuan-Rui Zhang (Phytochemistry, 2026)

Improving multi-step water demand forecasting performance: Static, past, future, and periodic feature importance - Rui Yuan; Yacan Man; Kuizu Su; Xiao Zhou; Shuming Liu (Journal of Water Process Engineering, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Transmission and migration of antibiotic resistance genes following agricultural fertilization in sloping croplands - Yifei Sun; Rui Chen; Sarah van den Broek; Jiong Wen; Yuxiang Li; Xibai Zeng; Shiming Su; Gina Garland (Journal of Hazardous Materials, 2026)

Ecosystem-specific composition and drivers of plastisphere resistome in freshwater and marine environments - Jianhong Shi; Chaoli Sun; Yinglong Su; Yifan Wu; Min Zhan; Chengyuan Ji; Rui Wang; Baoyi Lv (Environmental Research, 2026)

The couples' distinct effects of metals exposure on intermediate and pregnancy outcomes of in vitro fertilization treatment: A prospective cohort study - Qian Li; Xun Su; Zihan Xia; Duoxu Ji; Rui Dong; Tao Yin; Xinyu Yue; Dongyang Zhang; Yunxia Cao; Dongmei Ji; Chunmei Liang (Environmental Research, 2026)

Creep behavior and microstructural evolution of unsaturated red-bed mudstone under coupled matric suction-stress effects - Guoqing Cai; Fengjie Yin; Hengshuo Liu; Yanlin Su; Rui Yang (Engineering Geology, 2026)

Multi-Target Water Demand Forecasting with Graph Neural Networks: A Comparative Study - Yacan Man; Xiao Zhou; Rui Yuan; Kuizu Su; Shuming Liu (Water Resources Management, 2026)

Convex programming based method for stochastic optimal powered descent guidance with Wasserstein terminal cost - Wenjie Su; Haichao Gui; Rui Zhong (Advances in Space Research, 2026)

Seasonal variation and source apportionment of brown carbon light absorption in Tianjin, China: Insights from online monitoring and PMF modeling - Rui Qiao; Kaishe Su; Jingwen Zhang; Bolong Wang; Ziwei Zhan; Jinqiu Zhang; Jianhui Wu (Air Quality, Atmosphere & Health, 2026)

Urban perception analysis: integrating street view images with eye-tracking data - Jing Jin; Huifu Li; Rui Zhou; Su Li; Abdureyim Raxidin; Xun Zhang (Environment, Development and Sustainability, 2026)

Multifunctional deep learning-based mechanical-laser collaborative adaptive precision weeding system for lettuce - Rui Hu; Lei Kong; Wen-Hao Su; Bo-Wen Dong; Yujin Wang; Xiaobin Li; Yankun Peng (Computers and Electronics in Agriculture, 2026)

Developmental and cellular basis of sexual dimorphism in litchi (Litchi chinensis Sonn. cv. Feizixiao) - Jiakun Zheng; Chaoqiong Song; Weijian Sun; Xiuwen Feng; Xingling Su; Rui Xia; Zheng Qin (Plant Science, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Evolution of soil arching under different initial water-saturation conditions via coupled SPH-DEM method - Rui-Xiao Zhang; Dong Su; Xiang-Sheng Chen; Xiu-Song Shi; De-Jin Zhang (Computers and Geotechnics, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Can saturated fatty acids spare essential fatty acids in freshwater fish? Evidence from growth, metabolism and gut microbiota in common carp (Cyprinus carpio) - Yang Long; Zhiyi Cheng; Rui Li; Zeliang Su; Chaobin Qin; Guoxing Nie; Yuanyou Li; Dizhi Xie (Animal Feed Science and Technology, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

A novel peptide oyster-derived antimicrobial peptide against clinical carbapenem-resistant Acinetobacter baumannii - Rui Hou; Yihua Cai; Shida Xu; Dandan Ma; Ning Su; Shanshan Wang; Hongmei Mo; Mian Peng (Frontiers in Marine Science, 2026)
Background The escalating prevalence of multidrug-resistant pathogens, specifically carbapenem-resistant Acinetobacter baumannii (CR-AB), underscores the urgent need for novel antimicrobial strategies. Antimicrobial peptides (AMPs) offer a viable alternative to conventional antibiotics. Methods We discovered a novel AMP, designated OAMP, from oyster hemolymph and evaluated its antimicrobial efficacy against a spectrum of pathogens, including five clinical CR-AB strains. The synergistic potential of OAMP with meropenem, tigecycline, and colistin was assessed via checkerboard assays. Safety profiles were determined through cytotoxicity and hemolysis assays. Results OAMP exhibited potent broad-spectrum activity, effectively inhibiting CR-AB strains with MIC values of 4–8 µM. In combination therapies, OAMP demonstrated additive to synergistic effects with conventional antibiotics, facilitating a reduction in antibiotic dosage. However, safety assessments revealed cytotoxicity and hemolytic activity at MIC levels, indicating a narrow therapeutic window. Conclusions OAMP shows significant promise as a potent antibacterial agent and an effective adjuvant for combinatorial therapy against CR-AB. Future studies should focus on structural optimization to mitigate toxicity and enhance stability for clinical application.

Exopolysaccharides from Enterococcus faecium WH strain inhibit porcine epidemic diarrhea virus infection in vitro - Chenxi Li; Xiangchao Jia; Min Su; Rui Zhou; Zili Li (Veterinary Microbiology, 2026)

Dynamicomic analysis reveals the biocontrol activity of a Streptomyces avermitilis SM12 against Fusarium spp. - Xian Ma; Chenbo Jia; Jianyu Su; Wenyu Lu; Rui Zheng; Sijun Yue (Pesticide Biochemistry and Physiology, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Activation of the Tp53 apoptosis signaling pathway by chelidonine induces cardiac developmental abnormalities in zebrafish larvae - Jin Gu; Yanwen Zheng; Jian Su; Rui Li; Chiyu Zhang; Han Wang; Zhaomin Zhong (Chemico-Biological Interactions, 2026)

Mutant library construction and green fluorescent protein expression in a marine fungus capable of plastics biodegradation - Rui Liu; Yani Wang; Zhenjie Su; Jun Yang; Fan Fei; Rongrong Gao; Chaomin Sun (Journal of Oceanology and Limnology, 2026)